Phenazines as Disinfectants against Bacterial Leaf Blight of the Rice Plant - Oda, Makoto (1966)
A series of phenazine compounds, including 15 synthetics and a natural derivative, iodinin, were tested for inhibition of selected phytopathogenic bacteria and fungi. Eleven of the compounds had bacteriostatic activity for Xanthomonas oryzae. Three other species of Xanthomonas were resistant. Phenazine 5-oxide was the most effective phenazine against the bacterial leaf blight.